Dari Tradisi ke Ajaran Kajian tentang Sejarah Tahlilan, Dasar Keagamaan, dan Perannya dalam Budaya Islam Indonesia: From Tradition to Teaching: A Study of the History of Tahlilan, Its Religious Basis, and Its Role in Indonesian Islamic Culture - Rizqiyana, Shinta Alvy; Isdiyana, Aulia; Mutiara, Isnaeni; Muasyaroh, Rifqoh Latifatul; Susanto, Nanang Hasan (Litera Academica Publishing, 2026)
Indonesia is known as a country with diverse cultures, religions, and traditions that continue to thrive and develop within society. Among these various religious practices, tahlilan is one tradition that is still practiced by Muslims today. This study aims to deepen the understanding of the normative basis of tahlilan based on tauhid zikr, prayers for the deceased from the Quran and hadith, as well as its socio-cultural values such as solidarity and religious moderation. This study applies a qualitative research method that mainly relies on literature sources. The references used are from nationally and internationally accredited journals and scientific articles published in the last five years. This literature review is expected to broaden the understanding of the tahlilan tradition, thereby providing a solid foundation for analyzing the issues under study. Various previous studies have shown that tahlilan is the result of the acculturation of Islam with local culture since the Islamization of Java. As an implication, this study shows that the tradition of tahlilan has an important contribution in maintaining the balance between Islamic teachings and local culture.